Development of Syariah Fintech: Challenges and Opportunities in the Digital Economy: Pengembangan Fintech Syariah: Tantangan dan Peluang dalam Ekonomi Digital - Hasanah, Riska Ardila; Hasan, Zulfikar; Muhardi, Sona (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to analyze the challenges and opportunities in the development of Sharia Fintech in the digital economy era. Design/methodology/approach: This study employs a library research approach. The researchers identify, evaluate, and analyze literature that discusses Islamic economics, digital technology, and the integration between the two. Findings: The development of Islamic economics in the digital era faces various complex challenges. One of the main challenges is the low level of digital literacy among the target market of Islamic economics. Many individuals and small and medium enterprises (SMEs) have not fully understood or adopted digital technology, which hinders the integration of Islamic economic services with digital platforms. Research implications: The Sharia Fintech industry needs to enhance education and services to make them more accessible to the public. The government also needs to strengthen regulations and infrastructure to support the growth of this sector. Additionally, society must improve digital literacy to fully utilize Sharia Fintech services. Therefore, collaboration between industry, government, and society is crucial in building an inclusive and sustainable Islamic financial ecosystem in the digital era.